The effects of small-sided games on physical fitness in basketball players: a systematic review and meta-analysis - Zefeng Zhang; Jianhua Xu; Xiangbo Ji; Rui Chen (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background As a type of game-based training (GBT), small-sided games (SSGs) are often compared with non-game-based training (NGBT) in team sports. However, there is still no consensus on the chronic effects between SSGs and NGBT, including high intensity interval training (HIIT) and traditional technical drills (TTD), on physical performance in basketball players. Objective To systematically compare the chronic effects of SSGs versus NGBT on the physical fitness in basketball players through meta-analysis and to explore the moderator effects of training variables in SSGs. Methods A systematic search was conducted in databases including PubMed, Scopus, Web of Science, EBSCO host, and CNKI, covering the period from inception until December 13, 2023, with last updated on April 14, 2025. The meta-analysis, sensitivity analysis, publication bias detection and subgroup analysis were mainly conducted by Review Manager 5.3. The methodological quality of the included studies was assessed by the PEDro scale and the NOS scale. Results A total of 10 studies involving 253 subjects were included. The meta-analysis results indicated that: (1) No statistically significant differences were found between SSGs and NGBT for the improvement on aerobic and COD performance in basketball players (P > 0.05). And significantly higher enhancement of the lower limb explosive performance were found in SSGs compared with NGBT (SMD = 0.51, 95%CI: 0.20 to 0.82; P = 0.001). (2) Subgroup analysis revealed that SSGs programs favored a weekly training frequency ≥ 3 sessions (SMD = 0.60, 95%CI:0.08 to 1.13) in the improvement of aerobic performance and participants aged < 18 (SMD = 0.56, 95%CI:0.17 to 0.96) or training duration < 18.8 (SMD = 0.60, 95%CI:0.20 to 0.99) in the improvement of lower limb explosive performance. In addition, a higher enhancement of the lower limb explosive performance was found in SSGs versus TTD compared to SSGs versus HIIT (SMD = 0.78, 95%CI:0.33 to 1.22). Conclusions The evidence indicated that SSGs are as effective as NGBT for increasing aerobic and COD performance, and SSGs are more effective than NGBT for improving lower limb explosive performance in basketball players. Moreover, it is important to consider the influence of moderator variables such as weekly training frequency, age of participants and training duration when designing the SSGs programs. The findings provide consensus on the training effects of physical fitness between SSGs and NGBT, and offer directions for further research on optimal SSGs programs. Trial registration This study was registered with PROSPERO (ID. CRD42023483633).